The Religious Practices of Indonesian Students Studying in Turkey - Dalmi Iskandar Sultani; Cita Ayni Putri Silalahi; Sujarwo; Dinil Abrar; Naufa Hanif; Suci Amanda Putri; Fathin Nazirah Aulia (PT Inovasi Pratama Internasional, 2024)
The practice of religion for Indonesian students studying in Turkey deserves the attention of academics. This is because conditions, student backgrounds, distance and time differences between two countries can be factors in the fluctuations in the practice of religion for students. This research aims to prove whether Indonesian students in Turkey still consistently implement Islamic teachings. This research uses a qualitative research method with a case study approach to obtain in-depth data and information findings. The data collection technique used was interviews. The interview aspect is an important factor for student informants, to explore in detail and in depth about religious practices in Turkey. The research findings show that 1) Indonesian students still practice Islamic teachings while in Turkey, 2) Students use Islamic teachings and values as guidelines for carrying out daily activities and activities in Turkey, and 3) Students believe that religion is the basic motivation and guidance for life. strong and persistent in completing studies in Turkey.